The Effectiveness of Copyright Law No. 28 of 2014 in the Prevention of Copyright Infringement - Irhamdessetya, Hani; Daniel Manongga (The Virtual International Conference on Economics, Law and Humanities, 2023)
Copyright piracy has become a culture in Indonesia resulting in huge losses for creators and creative industries. In Indonesia, regulations relating to the protection of intellectual property rights have been in place for a long time. The development of laws and regulations governing intellectual property rights began in the1840s. However, the latest Copyright Act, Law No. 28 of 2014, has sparked much debate. This law is considered ineffective due to normative defects, such as adhering to copyright crimes, reducing or eliminating the responsibility of the apparatus or officials involved, and marginalising the rights of creators, resulting in low deterrent effect. The purpose of this article is to see how effectively the Copyright Act No. 28 of 2014 prevents copyright infringement. The results show that copyright is subject to the declaratory principle as intellectual property rights arise automatically after the creation. The frequent alternation of delicts gives the impression that Lawmakers do not have a history of copyright law. The purpose of the law is to ensure not only justice, but also compliance with the law. All laws will become ineffective if not enforced. So it is not just about the protection of citizens, it is also about citizens' compliance with the law. Law No. Article 28 contributes only to the protection of the personal rights of citizens; it does not guarantee the protection of the public rights of citizens.